Government Expenditure and Agricultural Sector Output in Nigeria (American Journal of Arts and Human Science, 2022)
The purpose of this study is to determine how government spending affects the output of the agricultural sector in Nigeria. This study deals with Nigeria’s government spending and agricultural sector output (1990-2020). Data for the study was sourced through the Central Bank of Nigeria (CBN) statistical bulletin 2020 as a secondary means. This study adopted the Ordinary Least Square (OLS) multiple regression method to analyze the data. Real gross domestic product was used as the dependent variable. At the same time, government expenditure on administration, government expenditure on social and community services, and government expenditure on economic services formed the independent variables. From the findings, it was discovered that the variables were positively insignificant to agricultural sector output at a 5% level of significance. Therefore, we conclude that government expenditure does not affect the agricultural sector output in Nigeria. Hence, it was recommended that the federal government of Nigeria through the Central Bank, should strengthen the banking sector to ensure an improved and efficient credit flow to the agricultural sectors because of its strategic importance in stimulating the growth and development of an economy.